Phase Relations in Ba6−3xLn8+2xTi18O54 (Ln = Nd & Sm) Electroceramics - Amanda L. Snashall; Yun Liu; Frank Brink; Ray L. Withers; Steven Cooper (Advances in Condensed Matter Physics)
A careful, systematic investigation of Ba6−3xLn8+2xTi18O54 (BLnTss) ceramics has been performed in order to understand the relationship between composition, microstructure evolution, and microwave dielectric properties. In this paper, we report the effects of composition, morphology, and sintering time on the phase relations and properties of BLnTss (Ln = Nd, Nd/Sm, Sm) ceramics. The microwave dielectric properties of the materials are reported in addition to phase characterisation and structural analysis via X-ray diffraction and field emission scanning electron microscopy coupled with energy dispersive X-ray spectroscopy. BLnTss, x=0.33, ceramics with high Sm content are found to experience a severe degradation of Qf and changes in τcf trending, associated with the onset of globular and needle-like grain morphology and a Ba-Ti rich phase. x=0.67 ceramics with high Nd content are found to exhibit a secondary phase (Nd2Ti2O7) upon prolonged sintering which resulted in beneficial changes to Qf and τcf without affecting εr. Two BLnTss ceramics compositions with near-zero τcf were successfully synthesised with high Qf and εr values.